Estimating the Outdoor Recreational Value of Chitgar Forestial Park of Tehran with the Use of Contingent Valuation Method (CV) - Kholuzini Sharahi, Majid; Mohamadi, Mohamad Hosein; Abedini, Azam (Journal of Economic Development, Environment and People, 2015)
Among issues related to the environment, one of the most important issues is pricing the environment. In the present study, the outdoor recreational value of Chitgar Jungle Park of Tehran and its visitors' willingness to pay per visit (WTP) were estimated by using Contingent Valuation method (CV) and 140 questionnaires based on dichotomous choice. The results revealed that 30 percent of the surveyed people were willing to pay an entrance fee and the mean willingness to pay for each visitor was estimated at 3076 Rials and its total annual recreational value was estimated at 5 billion Rials. Among the effective variables on individuals' visit of this park, recommendation, income, per-visit cost, family size, and visits during a year were 1% significant; park facilities and quality were 5% significant; and the visitors' use of personal vehicles, education, type of house, as well as job were 10% significant.